2021
DOI: 10.1101/2021.09.12.459854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling five dimensions of animacy in human brain and behaviour

Abstract: The perception of animate things is of great behavioural importance to humans. Despite the prominence of the distinct brain and behavioural responses to animate and inanimate things, however, it remains unclear which of several commonly entangled properties underlie these observations. Here, we investigate the importance of five dimensions of animacy: being alive, looking like an animal, having agency, having mobility, and being unpredictable in brain (fMRI, EEG) and behaviour (property and similarity judgment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Neuroimaging studies have shown that models of animacy (including humans/ animals, excluding plants) capture neural activity better than models of aliveness (including plants) (Contini et al, 2020;Jozwik et al, 2022). Our movement results suggest that this could be because plants move on a different global scale and frequency, the same explanation as others have provided for plant blindness (Wandersee & Schussler, 1999).…”
Section: Theoretical Implicationssupporting
confidence: 57%
“…Neuroimaging studies have shown that models of animacy (including humans/ animals, excluding plants) capture neural activity better than models of aliveness (including plants) (Contini et al, 2020;Jozwik et al, 2022). Our movement results suggest that this could be because plants move on a different global scale and frequency, the same explanation as others have provided for plant blindness (Wandersee & Schussler, 1999).…”
Section: Theoretical Implicationssupporting
confidence: 57%